Formation Pore Pressure Variation of the Neocomian Sedimentary Succession (the Fahliyan Formation) in the Abadan Plain Basin, SW of Iran - Bahman Soleimani; Mohammad Hassani-Giv; Iraj Abdollahi fard (Geofluids)
The Neocomian Fahliyan Formation is one of the important oil reservoirs in the Abadan Plain Basin, SW of Iran. To evaluate the pore pressure regime of the Fahliyan reservoir, 164 in situ pressure data points (MDT, XPT, and RFT) were analyzed from seven wells belonging to six oilfields. The pressure versus depth plot revealed that the Fahliyan reservoir is highly overpressured in all fields. The formation was characterized as a multilayered stacked reservoir with different pore pressure decreasing downward in a step-wise manner. Also, there is a major pressure step in the middle part of the reservoir, suggesting the presence of a regional efficient seal dividing the reservoir into two stacked compartments, where the upper compartment is more overpressured than the lower one. The stepped pressure pattern of the Fahliyan Formation is a regional phenomenon controlled by a factor governed regionally, the depositional condition, and facies lateral changes during the deposition of shallowing upward sequence of the Fahliyan reservoir. In addition, direct relationship is observed between the reservoir pressure and burial depth. This matter could amplify the initially generated overpressure state more possible due to dewatering of sediments and by-pass product of oil migration from Garau source rock to the Fahliyan reservoir.